THE RELATIONSHIP OF PARENTAL BEHAVIOR IN HANDLING ORALHYDRATION WITH DEHYDRATION IN TODDLERS WITH DIARHEA IN ENVIRONMENT VIII, SUMBER MULYO REJO VILLAGE, AST BINJAI DISTRICT NORTH SUMATRA, 2021 - Nurhikmah Panjaitan (Science Midwifery, 2021)
Based on data from the World Health Organization (WHO), there are almost 1.7 billion cases of diarrhea occurring in the world each year. Diarrhea is the second leading cause of child mortality. In Indonesia, children suffer from diarrhea more than 12 times per year, which is the cause of death for 15-34% of all causes of death. The primary treatment for diarrhea itself is to overcome the occurrence of dehydration. Rehydration therapy is very effective in reducing diarrhea mortality due to dehydration; by WHO in 2015, proper management of dehydration is using low osmolarity oral rehydration fluids such as Salt Sugar Solution or ORS. The preliminary study results are known; one of the efforts of parents in overcoming dehydration in their children who suffer from diarrhea is by giving fluids, but with the amount, frequency, and type of fluids that are not by the fluids needed by the body. Parents only give fluids when the child asks for and complains of feeling thirsty. The formulation of the problem in this study is "How is the Relationship between Parental Behavior in Handling Oralhydration with the Incidence of Dehydration in Toddler Children with Diarrhea, Sumber Mulyo Rejo Village, East Binjai District, North Sumatra in 2021. This type of research uses a correlation with a cross-sectional approach. The population and sample are parents—as many as 42 children under five and have experienced diarrhea (dehydration). The results showed the value of df = 2 and P-value = 0.002 less than 0.05 (0.002 < 0.05) then the hypothesis was accepted, so it can be concluded that there is a significant relationship between the behavior of parents in handling oral hydration with the incidence of dehydration in children under five with diarrhea. As a suggestion, it is hoped that health workers can educate parents about the management of dehydration and recognize signs of dehydration in children with diarrhea.